2019
DOI: 10.3389/fendo.2019.00158
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan Metabolic Pathways and Brain Serotonergic Activity: A Comparative Review

Abstract: The essential amino acid L-tryptophan (Trp) is the precursor of the monoaminergic neurotransmitter serotonin (5-hydroxytryptamine, 5-HT). Numerous studies have shown that elevated dietary Trp has a suppressive effect on aggressive behavior and post-stress plasma cortisol concentrations in vertebrates, including teleosts. These effects are believed to be mediated by the brain serotonergic system, even though all mechanisms involved are not well understood. The rate of 5-HT biosynthesis is limited by Trp availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
222
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 298 publications
(233 citation statements)
references
References 87 publications
3
222
0
8
Order By: Relevance
“…Returning to the microbiota, animal studies have reported that the serotonergic systems in the brain are influenced by gut bacterial composition, which in turn leads to GI problems and emotional disorders [60,63]. It is therefore expected that when the abundance of Trp-metabolizing bacteria such as Bacteroides and Clostridium increases, serotonin concentrations also increase as a result of their metabolic activity [64,65]. Meanwhile, lower levels of glutathione, homocysteine, methionine, and S-adenosylmethionine have been observed more in ASD children than in neurotypical children [66,67].…”
Section: Discussionmentioning
confidence: 99%
“…Returning to the microbiota, animal studies have reported that the serotonergic systems in the brain are influenced by gut bacterial composition, which in turn leads to GI problems and emotional disorders [60,63]. It is therefore expected that when the abundance of Trp-metabolizing bacteria such as Bacteroides and Clostridium increases, serotonin concentrations also increase as a result of their metabolic activity [64,65]. Meanwhile, lower levels of glutathione, homocysteine, methionine, and S-adenosylmethionine have been observed more in ASD children than in neurotypical children [66,67].…”
Section: Discussionmentioning
confidence: 99%
“…It may also be assumed that the icv KYNA injection alters the KYN pathway balance, resulting in increased nicotinamide adenine dinucleotide (NAD + ), which is responsible for the feedback inhibition of TDO. Thus it facilitates the shunt of TRP metabolism from the KYN pathways toward the SER pathways to increase SER production [10].…”
Section: Discussionmentioning
confidence: 99%
“…Initial studies were focused on the characterisation of kynurenine pathway in the biogenesis of nicotinamide adenine dinucleotide (NAD) (Badawy, 2017). However, recent studies link kynurenine pathway with neurodegenerative diseases, tumour proliferation, inflammation, immunity and depression (Badawy, 2017;Davis & Liu, 2017;Höglund, Øverli, & Winberg, 2019;Zhuravlev et al, 2016). Furthermore, L-tryptophan pathway was also reported to have a role during infections caused by virus like HIV (Lyons, Tovar-y-Romo, Thakur, McArthur, & Haughey, 2014) and bacteria like Rickettsia conorii (Feng & Walker, 2000) and A. phagocytophilum (Taank et al, 2017).…”
Section: Discussionmentioning
confidence: 99%